Biosorption of hexavalent chromium in a tannery industry wastewater using fungi species - D. Sivakumar (Global Journal of Environmental Science and Management)
The isolated fungi species of different kinds from chromium contaminated soil sites located in Nagalkeni, Chennai were used for reducing chromium(VI) in a tannery industry wastewater of Nagalkeni, Chennai.  The experiments were conducted to know biosorption potential of isolated fungi species for removing chromium(VI) in a tannery industry wastewater against the different pH, fungi biomass and chromium(VI) concentration (dilution ratio).  The results of this study indicated that the order of maximum removal of chromium(VI) by an isolated fungi species at an optimum pH of 3, fungi biomass of 4g andan initial chromium(VI) concentration of 18.125 mg/L (dilution ratio 4)is A. niger > A. flavus > A. fumigatus > A. nidulans > A. heteromorphus > A. foetidus > A. viridinutans.  This study found that the maximum removal of chromium(VI) was achieved by Aspergillus niger (96.3 %) than other fungi species at chromium(VI) concentration of 18.125 mg/Lin a tannery industry wastewater. The chromium removal from tannery industry wastewater was validated by checking chromium removal in an aqueous solution and by checking the removal efficiency of other parameters in a tannery industry wastewater using same isolated A. niger.  Biosorption model was proposed to simulate the experimental condition for removing chromium(VI) in a tannery industry wastewater by all isolated fungi species. The R2 and  values of the proposed model predicted that the proposed biosorption model is very much useful for predicting the trend of reduction potential of chromium(VI) in a tannery industry wastewater by all isolated fungi species.  This study suggested that one could select the type of fungi species, ion concentration level, selection of treatment period, quantity of biomass to be used, and pH level of the medium, to achieve the highest reduction of any toxic metals from any contaminated water, wastewater and soil environment.